Reflections by Bengt Ulf Östen Sonnerup - Sonnerup, Bengt (Frontiers in Astronomy and Space Sciences, 2022)
First, I will tell readers about memories of my graduate student days at Cornell. I will highlight some of my experiences there, and what I learned, and didn’t learn from them. Then I will then discuss a few of the research topics I have been working on over the years, including data interpretation and the tools for it, with special emphasis on the magnetopause. Aspects of MHD shocks and other structures, including boundary layers, are among those topics. I will mention a few people with whom I have worked closely and a few famous individuals, who influenced me in a significant way. The presentation contains material of potential interest to new, as well as more seasoned workers in the field. It will not always be in time order. 1. The author confirms that he has no commercial/financial interest in the work reported on in the paper 2. The author did all the research and wrote the paper. Preparation of the paper was supported by NASA grant 80NSSC19K0254 (Richard Denton, PI) to Dartmouth College.